Diagnostic Accuracy of a High-Sensitivity Cardiac Troponin Assay with a Single Serum Test in the Emergency Department. (1st August 2019) - Body, Richard; Twerenbold, Raphael; Austin, Catrin; Boeddinghaus, Jasper; Almashali, Malak; Nestelberger, Thomas; Morris, Niall; Badertscher, Patrick; McDowell, Garry; Wildi, Karin; Moss, Phil; Rubini Gimenez, Maria; et al.
Abstract: OBJECTIVES: We sought to evaluate diagnostic accuracy of a high-sensitivity cardiac troponin I (hs-cTnI) assay for acute coronary syndromes (ACS) in the emergency department (ED). The assay has high precision at low concentrations and can detect cTnI in 96.8% of healthy individuals. METHODS: In successive prospective multicenter studies ("testing" and "validation"), we included ED patients with suspected ACS. We drew blood for hs-cTnI [Singulex Clarity ® cTnI; 99th percentile, 8.67 ng/L; limit of detection (LoD), 0.08 ng/L] on arrival. Patients also underwent hs-cTnT (Roche Elecsys) testing over ≥3 h. The primary outcome was an adjudicated diagnosis of ACS, defined as acute myocardial infarction (AMI; prevalent or incident), death, or revascularization within 30 days. RESULTS: The testing and validation studies included 665 and 2470 patients, respectively, of which 94 (14.1%) and 565 (22.9%) had ACS. At a 1.5-ng/L cutoff, hs-cTnI had good sensitivity for AMI in both studies (98.7% and 98.1%, respectively) and would have "ruled out" 40.1% and 48.9% patients. However, sensitivity was lower for ACS (95.7% and 90.6%, respectively). At a 0.8-ng/L cutoff, sensitivity for ACS was higher (97.5% and 97.9%, ruling out 28.6% patients in each cohort). The hs-cTnT assay had similar performance at the LoD (24.6% ruled out; 97.2% sensitivity for ACS). CONCLUSIONS: The hs-cTnI assay could immediately rule out AMI in 40% of patients and ACS in >25%, with similar accuracy to hs-cTnT at the LoD. Because of its high precision at low concentrations, this hs-cTnI assay has favorable characteristics for this clinical application.